9r-11(-4r-4)=-2r+6(9r+9)

Simple and best practice solution for 9r-11(-4r-4)=-2r+6(9r+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9r-11(-4r-4)=-2r+6(9r+9) equation:



9r-11(-4r-4)=-2r+6(9r+9)
We move all terms to the left:
9r-11(-4r-4)-(-2r+6(9r+9))=0
We multiply parentheses
9r+44r-(-2r+6(9r+9))+44=0
We calculate terms in parentheses: -(-2r+6(9r+9)), so:
-2r+6(9r+9)
We multiply parentheses
-2r+54r+54
We add all the numbers together, and all the variables
52r+54
Back to the equation:
-(52r+54)
We add all the numbers together, and all the variables
53r-(52r+54)+44=0
We get rid of parentheses
53r-52r-54+44=0
We add all the numbers together, and all the variables
r-10=0
We move all terms containing r to the left, all other terms to the right
r=10

See similar equations:

| -3(5+4m)=-51 | | 8x+5/3=3x+1/5 | | 2m+40=800 | | 27=3(f-81) | | 23=-4=3b | | 3x+15+5x+25=180 | | 8+x=272 | | 2(-x-8)=-3(1+x) | | 3+m/9=4 | | -17+41=-4(x+1) | | 9x-34=-9x+18 | | 4(x+3)=(x+3)4 | | 295+39x=349+33x | | 15w-3w=4w-2w | | -r+3r=2 | | 5x/3+5=7x/5+3 | | 7/3y+5=26 | | 15+5x=4x+12 | | 5k+1=-9 | | 1m+50=100 | | 2-(1-3c)=2+2 | | 2x+12.41=25.15 | | 2(x+4.5)=15 | | –2q+–1=3 | | k+55/7=-6 | | 4(2x)=180 | | 8/x+9=4/2 | | 1200+30x=1200+50x | | -(n+1)=3 | | 1/2(x+50)=-3x-13+4x | | k=55/7=-6 | | -5(x-2)=2(x+5) |

Equations solver categories